G396 A prospective population study of the incidence of severe necrotising enterocolitis in England. (27th April 2016) - Battersby, CWS; Mandalia, S; Fitz-Simon, N; Costeloe, K; Modi, N
Abstract : Background: and aim Necrotising enterocolitis (NEC) is a potentially devastating gastrointestinal disease predominantly affecting very preterm infants. Uncertainty in relation to risk and preventive stratagems has resulted in varying clinical practices, especially in relation to enteral feeding. Here we investigate whether the incidence of severe NEC (defined as NEC leading to surgery or death) differs at network-level in England. Methods: We conducted a two-year, national population surveillance study of severe NEC (UKNC-NEC study). We extracted information from the National Neonatal Research Database. These data were verified with local study leads. We used multivariable logistic regression to identify patient characteristics associated with severe NEC. We calculated the unadjusted and adjusted incidence and the ratio of observed to predicted number of cases for each operational delivery network (ODN) and depicted this graphically using funnel plots. As the survival of preterm infants can inflate the incidence of NEC, we performed a sensitivity analysis with survival-free of NEC surgery as the outcome. Results: All ODNs (n = 13) comprising 163 neonatal units in England participated. During 2012–13, 118, 073 infants of all gestational ages were born and admitted to neonatal care; 529 died or received surgery for NEC (462 <32 weeks GA). Of infants that received surgery 33.0% (139/421) died. The incidence of severe NEC per 1000 admissions was highest for infants born 24 weeks (Figure 1 ). Low gestational age and growth restriction were significant independent predictors of severe disease. The incidence (95% CI) per 1000 preterm admissions (born <32 weeks) ranged from 20.0 (11.3 to 28.6) to 41.1 (26.9–55.2) across ODNs. The unadjusted funnel plot in Figure 1a illustrates that one ODN has an incidence of severe NEC which falls just outside the 95% control limits; however following adjustment for gestational age, birth weight SDS and antenatal steroids, all ODNs fall within the 95% control limits (Figure 1b ). The sensitivity analysis showed no evidence of variation in survival-free of NEC surgery at ODN-level. Conclusions: The incidence of infants receiving surgery for NEC in England is comparable to that reported in the literature for developed countries. We have shown no unusual variation in the incidence of severe NEC at network level in England.